Lessons Learned from Implementing a New Testing/Educational Tool for Patients Using an Insulin Pump - Stechova, Katerina; Vanis, Miroslav; Tuhackova, Martina; Urbaniec, Krzysztof; Kvapil, Milan (Diabetes technology & therapeutics, 2018)
BACKGROUND: To improve insulin pump therapy results, a special test for patients was devised. The model successfully used to achieve a license to operate different machines was followed. METHODS: The test (a practice and a full run, with a time limit) contained 42 questions, each with four optional choices, and could be answered online. Patients could familiarize themselves with the whole question pool first. Patients could repeat a full run attempt if they failed and were offered focused remedial education. The study group composed of adults, 46 females, and 54 males, all treated for type 1 diabetes, 38/100 newly introduced to insulin pump therapy. RESULTS: Eighty-five of 100 patients successfully completed their first full run attempt (80% or higher correct answers) and 3 of 100 on their second full run attempt; 12 of 100 patients were not able to succeed. The median of the test score was 2 mistakes (range 0-17 mistakes). The most problematic topics were diet and insulin regimens and their application. The crucial factor influencing the test score was the willingness to try practice run(s). Those who practiced had a significantly higher total test score with better results in 5 of 8 tested knowledge domains. Age and diabetes existing >15 years had an impact on the result, too. Both patients' and caregivers' opinions on the test were predominantly positive (or neutral). CONCLUSIONS: The type of test introduced is a good tool for checking a patient's theoretical knowledge and indirectly revealing a patient's level of motivation.
Keywords: zdraví - znalosti, postoje, praxe; osobnost; Female; Blood Glucose; vzdělávání pacientů jako téma; Humans; Motivation; Surveys and Questionnaires; motivace; Insulin Infusion Systems; lidé středního věku; Patient Education as Topic; inzulin; Personality; diabetes mellitus 1. typu; lidé; Health Knowledge, Attitudes, Practice; Hypoglycemic Agents; mužské pohlaví; krevní glukóza; průzkumy a dotazníky; Diabetes Mellitus, Type 1; dospělí; hypoglykemika; Male; ženské pohlaví; Insulin; Adult; Middle Aged; inzulinové infuzní systémy